A comparative study of radical radiotherapy with weekly paclitaxel versus radical radiotherapy with weekly cisplatin in the management of locally advanced squamous cell carcinomas of head and neck - Madhavan, Ram; P.K, Bhaskar; Nithiya, Antonoitte Mary; Kani, Janarthina; mathi, Madhu; P, Balasubramaniam; Kumar, Shanmuga (International Journal of Research in Medical Sciences, 2017)
Background: Concurrent chemo radiation is standard of care in locally advanced squamous cell carcinomas of head and neck. Single agent Cisplatin either weekly or three weekly is commonly used concurrently with radiation. The present study aims to evaluate the response rate and toxicity of radical radiotherapy with weekly paclitaxel and cisplatin in head and neck cancers. Methods: This is a prospective double arm study in which sixty patients with histologically proved squamous cell carcinomas registered in our department were accrued into the study with thirty patients in each arm. All patients were treated using Theratron phoenix 780 cobalt unit with a dose of 66 Gy in 33 fractions. The patients were randomized to receive 40 mg/m2 of weekly cisplatin or 40 mg/m2 of weekly Paclitaxel concurrently with radiation. The response to the therapy was assessed six weeks after completion of treatment. The statistical analysis was done using SPSS software. Results: In cisplatin group 18 patients achieved complete response and 12 patients achieved partial response whereas in Paclitaxel group 21 patients achieved complete response and 9 patients achieved partial response. However in paclitaxel arm the incidence of radiation dermatitis, mucositis, dysphagia and laryngitis are slightly higher compared to cisplatin group. Conclusions: The weekly paclitaxel concurrent with radiation is a feasible alternative to weekly cisplatin in locally advanced squamous cell carcinomas of head and neck.